Graphical simulation of numerical algorithms - an aproach based on code instrumentation and Java technologies - Balsa, Carlos (2012)
We want to create a working tool for mathematics teachers and a corresponding learning tool for students, namely a graphical simulator of mathematical algorithms (GraSMa). To achieve it we try two different strategies. We started by annotating manually the original algorithm with inspector functions. Now we are testing a new approach that aims at automatically annotating the original code with inspector functions. To achieve this we are developing a language translator module that enables us to comment automatically on any code written in Octave language. The run of the annotated code gated by one of these two ways, records in a XML (eXtensible Markup Language) file everything that happened during the execution. Subsequently, the XML file is parsed by a Java application that graphically represents the mathematic objects and their behaviour during execution. The final application will be accessed on-line through a website (WebGraSMa) which is currently under development. In this paper we report and discuss about the procedures followed and present some intermediate results.